Regulation of Thermally Activated Delayed Fluorescence to Room‐Temperature Phosphorescent Emission Channels by Controlling the Excited‐States Dynamics via J‐ and H‐Aggregation. Issue 33 (7th July 2021) - Li, Shuai; Fu, Liyuan; Xiao, Xiaoxiao; Geng, Hua; Liao, Qing; Liao, Yi; Fu, Hongbing
Abstract: Control of excited‐state dynamics is key in tuning room‐temperature phosphorescence (RTP) and thermally activated delayed fluorescence (TADF) emissions but is challenging for organic luminescent materials (OLMs). We show the regulation of TADF and RTP emissions of a boron difluoride β‐acetylnaphthalene chelate ( β CBF2 ) by controlling the excited‐state dynamics via its J‐ and H‐aggregation states. Two crystalline polymorphs emitting green and red light have been controllably obtained. Although both monoclinic, the green and red crystals are dominated by J‐ and H‐aggregation, respectively, owing to different molecular packing arrangements. J‐aggregation significantly reduces the energy gap between the lowest singlet and triplet excited states for ultra‐fast reverse intersystem crossing (RISC) and enhances the radiative singlet decay, together leading to TADF. The H‐aggregation accelerates the ISC and suppresses the radiative singlet decay, helping to stabilize the triplet exciton for RTP. Abstract : J‐aggregates significantly reduce the energy gap between the lowest singlet (S1 ) and triplet (T1 ) excited states and contribute to the reverse intersystem crossing (RISC) process; while H‐aggregates will accelerate ISC and suppress radiation transition of S1 to realize phosphorescence. This provides crucial information for the deep undrstanding of the internal mechanism of the excited state dynamics controlled by different aggregates.